Characterisation of ammonia emissions from gasoline and gasoline hybrid passenger cars - Farren, Naomi J.; Davison, Jack; Rose, Rebecca A.; Wagner, Rebecca L.; Carslaw, David C. (Atmospheric Environment: X, 2021)
Recent evidence suggests NH3 emissions from road vehicles play an important role in the formation of fine particulate matter, especially in urban areas. However, there is little data available for NH3 emitted from road vehicles under real driving conditions, in part due to its lack of regulation in vehicle emission legislation. In this study, we use 210,000 vehicle emission remote sensing measurements to evaluate the complex mix of factors affecting NH3 emissions from gasoline and gasoline hybrid passenger cars. The influence of vehicle model year and manufacturer on NH3 emissions is considered, as well as the effect of vehicle deterioration. It is found that the amount of NH3 emitted increases as vehicle mileage increases. A comparison of cold start and hot exhaust NH3 emissions reveals that on average, cold start emissions are a factor of 1.7 times higher. New NH3 emission factors are developed, in addition to speed-emission curves that are potentially useful for national inventories. A new application of remote sensing data is reported, whereby the proportion of failed CO2 measurements for hybrid vehicles provides unique insight into the real world battery use of both conventional hybrid electric and plug-in hybrid electric vehicles, which is used to refine the NH3 emission factors for these vehicles. [Display omitted] •Vehicle emission measurements using remote sensing.•New NH3 emission factors for gasoline and gasoline hybrid cars.•Quantification of NH3 cold start penalty.•NH3 increases with increasing vehicle mileage.•Fraction of failed CO2 measurements gives unique insight into hybrid battery use.